Serum IgE levels in patients with ataxia telangiectasia - Özkaragöz, Fatih; Yeniay, İhsan; Yeğin, Olcay; Sanal, Özden; Ersoy, Fügen; Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1983)
The serum IgE levels in 15 At patients were investigated and compared with those of normal individuals. The correlation of IgE with various immunological parameters is discussed.
Keywords: ataxia telangiectasia; immunoglobulin E